Effect of clomiphene citrate on the quality of cervical mucus in infertile women - Jusuf, Elizabeth Catherine (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To describe the effect of clomiphene citrate on the quality of cervical mucus in infertile women. Method: This study is a non-randomized clinical trial. The study was carried out at several education hospitals in Makassar from March 2008 to April 2009. The subjects of the study were infertile women who fulfilled the inclusion criteria with intervention study. The statistical analysis was performed using Wilcoxon Sign-ed Rank Test with Î± 5%. Result: There were 36 cases found, and most were in the range of 26 - 30 years old (38.9%), university level education (50%), civil servant (47.2%), normal nutritionals status (55.5%), regular menstruation cycle (94.4%), marriage length 1 - 5 years (52.8%), and previously treated (61.1%). There was a significant difference of the cervical mucus quality in the infertile women before and after the administration of clomiphene citrate which tend to become worse (p = 0.012). At previously CC-treated group, it was found that after the administration of clomiphene citrate, the quality of cervical mucus tend to be worse (100%). Conclusion: The administration of clomiphene citrate tends to have declining effect on cervical-mucus quality of infertile women. [Indones J Obstet Gynecol 2010; 34-2: 73-6] Keywords: clomiphene citrate, quality of cervical mucus, infertile women